PENGEMBANGAN PRODUK OLAHAN TEPUNG SAYURAN DI DESA SINDON KECAMATAN NGEMPLAK KABUPATEN BOYOLALI - Muhtadi, Muhtadi; Rauf, Rusdin; Harismah, Kun; Saifuddin, Saifuddin (Universitas Muhammadiyah Surakarta, 2016)
In the Pemitra community service activities for Product Development Processed Vegetables in Desa Sindon, Ngemplak Boyolali, has been done by training, and assistance to the women of PKK, Aisyah and âMawarâ farmers group in Desa Sindon to improve the understanding, skills and marketing development products processed from starchy vegetables. In this Pemitra had conducted training activities to product of starchy vegetables, then trained the skill of making a wet noodle, instant noodles, crackers and biscuits from flour processed vegetables. The results that have been obtained from this Pemitra activities all women partners group have been able to get the skills to cultivate vegetable flour into wet noodles, instant noodles, crackers and biscuits. However, constraints and problems still faced was to start a business production and developing marketing of products processed starchy vegetables group of women who fostered still very low, so the follow-up to the next community services activities will be focused on to accompany the women group of PKK, Aisyah and farmers âMawarâ in terms of development, production, packaging, licensing P-IRT and marketing of products from starchy vegetables.